The ripple effect: How leader workplace anxiety shape follower job performance - Zhang, Shanshan; Chen, Lifan; Zhang, Lihua; Stein, Aaron McCune (Frontiers in Psychology, 2022)
Although the dominant view in the literature suggests that work-related anxiety experienced by employees affects their behavior and performance, little research has focused on how and when leaders’ workplace anxiety affects their followers’ job performance. Drawing from Emotions as Social Information (EASI) theory, we propose dual mechanisms of cognitive interference and emotional exhaustion to explain the relationship between leader workplace anxiety and subordinate job performance. Specifically, cognitive interference is the mechanism that best explains the link between leader workplace anxiety and follower task performance, while emotional exhaustion is the mechanism that best explains the link between leader workplace anxiety and follower contextual performance. Additionally, we examine how follower epistemic motivation serves as a boundary condition for the effect of leader anxiety on follower performance outcomes. Results from a 2-wave study of 228 leader-follower dyads in a high-tech company mostly supported our theoretical model. We conclude the study with a discussion of the theoretical and practical implications of our findings.